Protective effect of Yemeni green coffee powder against the oxidative stress induced by Ochratoxin A. (2020) - Nogaim, Qais A.; Sai Pratyusha Bugata, Lakshmi; PV, Prabhakar; Reddy, Utkarsh A.; P, Mangala Gowri; S, Indu Kumari; M, Mahboob
Graphical abstract: Highlights: Determination of antioxidant activity of green Yemeni coffee powder against Ochratoxin-A in female albino Wistar rats. This is a 28 days repeated dose study - 5 groups of rats were treated with their respective doses. On termination of the study lipid peroxidation, reduced glutathione, activities superoxide dismutase, catalase and glutathione reductase assays of liver, kidney and brain was carried. Histopathology of liver, kidney and brain was studied. Concomitant treatment of Yemeni green coffee with Ochratoxin A has shown dose dependent antioxidant effect on induced oxidative stress. Abstract: The current study focusses on knowing the antioxidant effects of green Yemeni coffee powder on reducing the oxidative stress that was induced by Ochratoxin A in kidney, liver and brain of rats. The grouping of female albino Wistar rats was into 5 groups (5 rats/group). Rats of Group 1 designated Vehicle Control (only water), Group2 (10 mg/kg Ochratoxin A); Group 3 designated Low dose (2000 mg/kg Coffee+10 mg/kg Ochratoxin A); Group 4 designated High dose (4000 mg/kg Coffee+10 mg/kg Ochratoxin A); Group 5 designated Coffee Control (1000 mg/kg Coffee) and orally administered with the above test materials repeatedly every day for 28 days. On termination of the study, liver, brain and kidney tissues were collected after dissection, oxidative stress biomarkers (Levels of Lipid Peroxidation and Reduced Glutathione, activities Superoxide Dismutase, Catalase and Glutathione Reductase enzymes) and histopathological studies were carried out. Treatment of Ochratoxin A alone (group 2 rats) significantly increased malondialdehyde content, catalase, and glutathione reductase activities with a decrease in the activity of superoxide dismutase enzyme and reduced glutathione level and in brain, kidney and liver. Whereas, low dose coffee (group 3) and high dose coffee (group 4) rats showed dose-dependent increase in antioxidant and less histopathological alterations. Concomitant treatment of Yemeni green coffee powder and Ochratoxin A brought dose-dependent protective effects against oxidative stress which was induced using Ochratoxin A in liver, brain, and kidney tissues of female rats.